2014
DOI: 10.7314/apjcp.2014.15.5.2267
|View full text |Cite
|
Sign up to set email alerts
|

Breast, Cervix and Colorectal Cancer Knowledge among Nurses in Turkey

Abstract: Background: Cancer is one of the most common causes of death in Turkey. Nurses are essential providers of preventive care for patients, especially breast, cervical and colorectal cancer screening as part of routine preventive practice. The aim of this study was to assess knowledge of these cancers among nurses in Karabuk State Hospital. Materials and Methods: This cross-sectional and descriptive study was performed from April 1 to July 30, 2013. The study sample consisted of 226 nurses working in Karabuk State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 18 publications
2
33
0
6
Order By: Relevance
“…These findings are support by Akhtari-Zavare et al (2013) that reported 97% of the participants heard about BSE, only 36.7% stated that they performed BSE and among those who practice BSE, most of them practice BSE occasionally (50, 57.5%). Similarly, in a study from Turkey reported less than half of the respondents participated BSE and a few are doing BSE regularly (Andsoy and Gul, 2014). All these studies showed that Asian women have low to moderate knowledge with poor to moderate BSE practice.…”
Section: Discussionmentioning
confidence: 88%
“…These findings are support by Akhtari-Zavare et al (2013) that reported 97% of the participants heard about BSE, only 36.7% stated that they performed BSE and among those who practice BSE, most of them practice BSE occasionally (50, 57.5%). Similarly, in a study from Turkey reported less than half of the respondents participated BSE and a few are doing BSE regularly (Andsoy and Gul, 2014). All these studies showed that Asian women have low to moderate knowledge with poor to moderate BSE practice.…”
Section: Discussionmentioning
confidence: 88%
“…In this study, all female students showed have knowledge about breast cancer and their awareness of breast cancer has a good level. The earlier studies on women in Turkey breast cancer of women in early diagnosis information and has been found to be insufficient (Cadir et al, 2004;Findik and Turan, 2004;Andsoy and Gul, 2014;. In the studies conducted by Sambanje and Mafuvadze (2012) and Al-Sharbatti et al (2013) unlike the medical and non-medical university students studying in sections in all of the knowledge and awareness of breast cancer has been reported to be low.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that the breast cancer accounts for 30-40 % of all the cancer incidences in women all over the world (Andsoy and Gul, 2014;Che et al, 2014;Rizalar et al, 2014). In Turkey, breast cancer incidence rates are rapidly increasing (Andsoy and Gul, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sreedharan et al investigated knowledge and practice of breast self exam in 154 nurses working in the United Arab Emirates hospitals via a self-administered structured questionnaire and made out satisfactory results (Sreedharan et al, 2010). Yousuf et al examined general knowledge about breast cancer and its risk factors in 210 Saudi nurses practicing in primary health care centers (Yousuf et al, 2012) while Fotedar et al investigated the knowledge of nurses about breast cancer risk factors and methods of early detection in 457 nurses in a medical college in India (Fotedar et al, 2013); Ozkan et al assessed the level of knowledge as well as beliefs about breast self examination in 113 nursing and midwifery students (Ozkan et al, 2010) and Andsoy et al carried out a study to investigate knowledge of breast, cervical and colorectal cancer screening among 226 working nurses (Andsoy and Gul, 2014). All these researchers concluded that adequate awareness about the subject may be raised in nurses by establishing continuing education programs.…”
Section: Discussionmentioning
confidence: 99%